ESTIMASI RELIABILITAS MENGGUNAKAN ESTIMATOR MAKSIMUM LIKELIHOOD YANG DIMODIFIKASI DARI DISTRIBUSI EKSPONENSIAL - , Yani ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The estimation of reliability is an estimation that describes an assessment of reliability of particular component, in which and are independent random variables where represents the strength and represents the stress. The most important element in this estimation is the existence of parameters from distribution random variables and . In this thesis, we discussed the estimation of reliability of two parameters exponential distribution where and had common location parameter but different scale parameter. Scale parameters were estimated using a modified maximum likelihood estimator, while location parameter was estimated using consistent alternative estimator. In the data simulation, we calculate the confidence interval of using asymptotic distribution of . The result of the present study shows that for , , and samples with , and , in observation interval with 95% confidence interval.